ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI TINGKAT PENYELESAIAN TINDAK LANJUT REKOMENDASI HASIL PEMERIKSAAN BPK RI PADA PEMERINTAH DAERAH DI PULAU JAWA DAN BALI - Pipit Siti Jenar Puspitasari; Dwi Ratmono (Diponegoro Journal of Accounting, 2017)
This research aims to analyze the factors that influence follow-up of audit recommendation. The independent variables that tested in this study are auditor's professional skills, the type of local government, the number of accounting entities, tenure regional head, the age of local government, the dependance level and legislative oversight.This study uses secondary data derived from a detailed list of BPK’s follow-up Audit on the District and City government in Java and Bali for the period up to 2015. The research sample of 122 district and city in the province of West Java, Central Java, East Java, Banten, Yogyakarta and Bali. The analytical method used is multiple linear regression analysis.The results show that auditor's professional skills have positive affect to follow-up of audit recommendation. Meanwhile the type of local government, the number of accounting entities, tenure regional head, the age of local government, the dependance level, legislative oversight do not affect the follow-up of audit recommendation.